Profil Gizi dan Kandungan Kolesterol Udang Windu (Penaeus monodon) dengan Metode Pemasakan Berbeda: Chemical and Cholesterol Content of Tiger Shrimp (Penaeus monodon) with Different Cooking Methods - Ikbal Syukroni; Andi Santi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Tiger shrimp (Penaeus monodon) is one of the consumption shrimp whose economic value continues to increase and is widely consumed by the community. This research aimed to determine the effect of chemical and cholesterol content of tiger shrimp with different cooking methods which is boiling, steaming and deep frying for 10 minutes each, fresh tiger prawns were used as control. The results showed that tiger shrimp that were given cooking with boiling tended to change the chemical content which was not much different from the control, moisture 71.93%, ash 3.25%, protein 18.82% and lipid 2.07%. Processing of tiger shrimp using the steaming method showed a low cholesterol value of 1.69 mg/100 gr. Based on the results of the study, it can be concluded that processing processes such as boiling, steaming and deep frying method have an influence on the chemical content of tiger shrimp. Steaming processing method can reduce cholesterol content in tiger prawns as much as 94.12%.